What Is What Is The Optimal Tax Treatment That Motivates Donor Corporations To Make More Monetary And In-Kind Donations To Their Communities And With Minimal Damage To The Interests Of All The Parties Involved, And The Content Of The CSR Idea? - Younis A. Battal Saleh (Entrepreneurship Faculty, Universitas Garut, 2020)
ABSTRACT: This theoretical study attempted to answer the following question: What is the optimal tax treatment that motivates donor corporations to make more monetary and in-kind donations to their communities and with minimal damage to the interests of all the parties involved, and the content of the CSR idea? To answer this complex question, the researcher was forced to imagine all possible tax treatment methods for corporate monetary and in-kind donations and to determine their advantages and disadvantages -according to certain criteria, to choose the optimal tax treatment method. This study recommends the adoption of the method of government's rights and then corporation's rights in government's rights